Perbanyakan Lili (Lilium longiflorum Thunb.) Secara In Vitro dengan Zat Pengatur Tumbuh BAP dan NAA - Deswiniyanti, Ni Wayan; Lestari, Ni Kadek Dwipayani; Astarini, Ida Ayu; Hardini, Yunita (Jurnal Hortikultura Indonesia, 2020)
Lily plant (Lilium longiflorum Thunb.) is an ornamental and cut flower. The demand for cut lily flowers has a promising demand, but the availability of seedling is llimited. This study consisted of in vitro germination of lily seeds on ½ Murashige & Skoog (MS) medium, multiplication of base and shoot-tip explants in various treatments of MS medium with the combination of plant growtht regulator (PGR) BAP and NAA. The aims of this research were to obtain the appropriate combination of media and the parts of explants of growing shoots, roots and callus.The combinations of MS medium with BAP and NAA are (a)control 0:0 mg L-1, (b)0:0.1 mg L-1, (c)0:1 mg L-1, (d)0.1:0 mg L-1, (e)0.1:0.1 mg L-1, (f)(0.1:1 mg L-1), (g)1:0 mg L-1, (h)0.1:1 mg L-1, (i)1:1 mg L-1. The research were arranged as factorial design with two factor in Randomized Complete Block Design (RCBD). The first factors were combination of BAP and NAA, and the second one was the types of explant (base part of shoot and shoot tip). Lily seeds were succesfully germinated as much as 58%. Medium c and i succesfully induced explants to grow buds, roots and callus. Medium c induced shoots, roots and callus, meanwhile medium i induced roots and callus. Percentage of response growth of shoot base explants were 11.1% shoot growth and 13.3% roots, while shoot tip explants only showed 6.7% root growth without shoot growth. The growth of callus showed the same results on the base and shoot tip explants (4.4%).